Mpox: An emerging or re-emerging infection with a potential colossal burden on healthcare globally - Chikwelu L. Obi; Nqobile M. Mkolo; Liziwe L. Mugivhisa; Modupe O. Ogunrombi; Mukhethwa M. Mphephu; Clarissa M. Naidoo (African Journal of Laboratory Medicine)
The World Health Organization identified mpox (formerly known as monkeypox), as a resurgent zoonotic epidemic caused by the mpox virus. It is an emerging and re-emerging pathogen with a range of hosts and geographical distribution worldwide. Peer-reviewed scientific articles from 1958 to 29 August 2024 related to global mpox research were extracted from Web of ScienceTM Core Collection and Google Scholar Databases to gauge the extent of the infection. Mpox is marked by a recent resurgence of infections across continents, with Africa being the hardest-hit region. The mpox re-emergence has shown a new mechanism of transmission, with several causes such as a rise in the number of unvaccinated individuals, behaviour risk factors, waning immunity, genetic evolution, and environmental circumstances. Preventive and control measures of mpox include vaccination and patient isolation, while treatment involves antivirals and antibiotics for secondary bacterial infections. Laboratory diagnosis entailing polymerase chain reaction can be effective for routine purposes, but results of serological tests must be interpreted with caution, because of cross-reacting determinants among orthopoxviruses. The structure and classification of the mpox virus, clinical manifestations, pathophysiology, epidemiology, historical antecedent, therapeutics, vaccines, and laboratory diagnosis of the disease are explicated, showcasing mpox as an emerging or re-emerging infection with a potential colossal burden on healthcare, and its classification as an international public health emergency by the World Health Organization.